Adverse pregnancy outcome and its association with the various determinants of current pregnancy in a district hospital, urban Bengaluru, India - Hoysanahalli Shivashankarappa, Darshan; Joy, Neha Annet; M. D., Sangeetha (International Journal Of Community Medicine And Public Health, 2024)
Background: Maternal health is a crucial aspect of public health, directly influencing pregnancy outcomes. Adverse outcomes, such as miscarriage, stillbirth, cesarean delivery, and abortion, reflect poor maternal health and contribute to maternal mortality and infant mortality rates. Antenatal care (ANC) and institutional delivery are pivotal strategies to mitigate maternal and fetal complications. However, the escalating rates of cesarean sections in India, surpassing the WHO-recommended threshold, present a severe public health challenge. Methods: This retrospective cross-sectional study, conducted in urban Bengaluru from January to July 2023, aimed to identify adverse pregnancy outcomes and their determinants among women aged 15 to 49 in India. Data from maternal birth and labor records were analyzed, encompassing sociodemographic factors, obstetric characteristics, and adverse outcomes. Results: The study revealed a 20.8% magnitude of adverse pregnancy outcomes. It was found to be higher among women in the age group above 30 years, multigravida, have low blood pressure (BP) both systolic and diastolic, B blood group, positive Rh type, a male baby. In bivariate analysis, higher odds were observed among women in the 30-49 age group, body mass index overweight category, active management of the third stage of labor, and delayed cord clamping were found to be statistically significant. Conclusions: The study underscores the urgency for an expanded action plan to enhance maternal healthcare in India. While governmental initiatives exist, there remains a pressing need to address unnecessary caesarean deliveries and associated complications. The findings advocate for heightened awareness, community health worker training, and stringent guidelines on the necessity of caesarean sections.